Efforts to Improve Listening Skills Through Storytelling Methods Using Ritatoon Media in Children - Sar'an, Sar'an; Nasution, Soibatul Aslamiah; Dina Septiana, Yulda; Fitriani, Wita; Dwi Wulandari, Viona; Dwi Utami, Rahmi (Institute of Research and Community Service STAI Yayasan Tarbiyah Islamiyah Kota Padang, 2025)
This study aims to determine the learning process, improvement of listening skills, as well as supporting and inhibiting factors in the application of the storytelling method using the ritatoon media for children at ABA Paraman Ampalu Kindergarten. Using a qualitative research method with a case study approach through interviews, observation, and documentation, the results of the study indicate that the storytelling method using the ritatoon media is effective in improving children's listening skills. The learning process is carried out through the stages of preparation, implementation, evaluation, and reflection. The ritatoon media has been proven to be able to attract children's attention so that they are more focused on listening to the story, while improving listening skills occurs through the selection of appropriate stories, interactive storytelling processes, and supporting activities. Supporting factors for success include the use of ritatoon media, interesting storytelling methods, and support from teachers and parents, while obstacles faced are limited access to media, teacher skills in telling stories, and lack of parental support at home.